A large‐scale survey of pairwise epistasis reveals a mechanism for evolutionary expansion and specialization of PDZ domains. Issue 8 (4th March 2021) - Nedrud, David; Coyote‐Maestas, Willow; Schmidt, Daniel
Abstract: Deep mutational scanning (DMS) facilitates data‐driven models of protein structure and function. Here, we adapted Saturated Programmable Insertion Engineering (SPINE) as a programmable DMS technique. We validate SPINE with a reference single mutant dataset in the PSD95 PDZ3 domain and then characterize most pairwise double mutants to study epistasis. We observe wide‐spread proximal negative epistasis, which we attribute to mutations affecting thermodynamic stability, and strong long‐range positive epistasis, which is enriched in an evolutionarily conserved and function‐defining network of "sector" and clade‐specifying residues. Conditional neutrality of mutations in clade‐specifying residues compensates for deleterious mutations in sector positions. This suggests that epistatic interactions between these position pairs facilitated the evolutionary expansion and specialization of PDZ domains. We propose that SPINE provides easy experimental access to reveal epistasis signatures in proteins that will improve our understanding of the structural basis for protein function and adaptation.